Socioeconomic Inequality in Health Care Utilization: A Study of Service Utilization in Yazd, Iran - Najmeh Baghian; Elham Tayefi; Mohammad Ranjbar; Adel Eftekhari (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Determining the inequality in health and the gap level among various socio-economic groups and factors affecting it were always concerns of most politicians and social scientists. This study investigated inequality in utilization of health care among Yazd residents in 2014. Methods: This analytic and cross-sectional study was conducted in 2014. The participants were all households of Yazd. The data were collected through a three-part questionnaire including demographic factors, socio-economic factors, and utilization of health services. The number of samples was estimated to be 1037 households selected by random stratified sampling. After administrating the questionnaire in the form of interview, data were entered into the SPSS software.  Later, factor analysis method was carried out and participants were categorized based on their social and economical status. Afterwards, using the logistic regression method, the correlation among variables was calculated and finally, for measuring the concentration index, the stratified data were fed into Stata11 software version 12/SE and analyzed. Results: According to the findings, there was no meaningful inequality in the distribution of contagious and non-contagious decreases in the population under study. Inequality in utilization of services for inpatient and outpatients during the past 6 months in the five socio-economic groups was significant (P-value = 0.000). This shows that accumulation of visits occurred in richer groups of society. Also, it can be claimed that self-treatment has greater accumulation in the poorer quintiles (CI = -0.09). Conclusion: Inequality in benefitting from health services reflects the economical situation of households. As a result, it is expected that by taking steps to improve the living conditions, the equity in service utilization will be increased.